2009
DOI: 10.1103/physrevlett.102.045901
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Diffusion Mediated by Atom Deposition into a Porous Substrate

Abstract: Constant flux atom deposition into a porous medium is shown to generate a dense overlayer and a diffusion profile. Scaling analysis shows that the overlayer acts as a dynamic control for atomic diffusion in the porous substrate. This is modeled by generalizing the porous diffusion equation with a time-dependent diffusion coefficient equivalent to a nonlinear rescaling of time.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 17 publications
7
61
1
4
Order By: Relevance
“…Pascal Brault (1) (Pascal.Brault@univ-orleans.fr), Jean-Marc Bauchire (1) , Amaël Caillard (1) , Anne-Lise Thomann (1) , Mathieu Mougenot (1,2) , Christophe Coutanceau (3) , Steve Baranton (3) , Pascal Andreazza (4) , Caroline Andreazza-Vignolle (4) , François James (5) et Christophe Josserand (6) …”
Section: Les Piles à Combustibleunclassified
See 2 more Smart Citations
“…Pascal Brault (1) (Pascal.Brault@univ-orleans.fr), Jean-Marc Bauchire (1) , Amaël Caillard (1) , Anne-Lise Thomann (1) , Mathieu Mougenot (1,2) , Christophe Coutanceau (3) , Steve Baranton (3) , Pascal Andreazza (4) , Caroline Andreazza-Vignolle (4) , François James (5) et Christophe Josserand (6) …”
Section: Les Piles à Combustibleunclassified
“…L'élaboration de la phase catalytique est alors directement liée au problème de transport/diffusion/ agrégation/croissance en milieu poreux. Pour traiter le problème, nous avons mis en place trois approches : une étude théorique de la « diffusion » du platine dans la couche poreuse [5,6], une étude de la répartition des agrégats dans le milieu poreux par diffusion des rayons X aux petits angles en incidence rasante (GISAXS), et une étude par microscopie électronique en transmission à haute résolution (HRTEM) [7].…”
Section: Pulvérisation Plasmaunclassified
See 1 more Smart Citation
“…The Pt depth profile for an electrode loaded with 0.01 mg Pt cm -2 , as presented elsewhere, showed that platinum penetrates down to 500 nm inside the diffusion layer. This rather important penetration depth is due to the deposition method, which allows depositing atoms with high kinetic energy [11,12]. A four-step process occurs during deposition: transport in the porous layer pores, adsorption on carbon particle surface, platinum diffusion on the carbon particles and Pt cluster growth.…”
Section: Characterizations Of Catalystsmentioning
confidence: 99%
“…A major class of anomalous diffusion is subdiffusion. It is a rather general process and has been observed in such as atomic transport in porous substrates [4], cell migration in vivo [5], enzymatic binding in crowded cellular environments [6], local viscoelastic response in actin networks [7], and conformational fluctuation of protein molecules [8][9][10][11]. One of the mechanisms leading to subdiffusion is chain-dynamics-induced distance fluctuations [12], such as in the Rouse model, which has been used extensively in studies of polymers [13].…”
Section: Introductionmentioning
confidence: 99%